Current Issues of Forecasting in Physical Education and Sports Today - Khamrayeva, Z. B. (European Journal of Life Safety and Stability (2660-9630), 2021)
At present, the problem of scientific forecasting is relevant for many spheres of public life, including physical culture and sports. The importance of developing the problem of forecasting in the field of sports is due to the need to search for new ways of training qualified athletes. Forecast is a probabilistic scientifically grounded judgment regarding the possible ways to achieve the athlete's condition, defined as a goal. Forecasting is a type of human cognitive activity aimed at forming forecasts for the development of an object based on an analysis of trends in its development. The purpose of forecasting is mental anticipation of the desired results of sports activity. Forecasts are based on the methods that accompany every scientific research: analysis and synthesis, deduction and induction, observation, experiment, systematization and classification, intuitive foresight and hypothesis, analogy, extrapolation.